2019
DOI: 10.1101/2019.12.19.882183
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Self-organization in brain tumors: how cell morphology and cell density influence glioma pattern formation

Abstract: AbstractModeling cancer cells is essential to better understand the dynamic nature of brain tumors and glioma cells, including their invasion of normal brain. Our goal is to study how the morphology of the glioma cell influences the formation of patterns of collective behavior such as flocks (cells moving in the same direction) or streams (cells moving in opposite direction) referred to as oncostream. We have observed experimentally that the presence … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 36 publications
(47 reference statements)
1
6
0
Order By: Relevance
“…2, B and C). As predicted by our in silico model (5) these results suggest that cell shape, or eccentricity, is involved in the organization of collective motion patterns.…”
Section: Oncostreams: Multicellular Fascicles Of Elongated Tumor Cellsupporting
confidence: 81%
See 1 more Smart Citation
“…2, B and C). As predicted by our in silico model (5) these results suggest that cell shape, or eccentricity, is involved in the organization of collective motion patterns.…”
Section: Oncostreams: Multicellular Fascicles Of Elongated Tumor Cellsupporting
confidence: 81%
“…This group studied ex-vivo explant slices of spontaneous intestinal carcinoma, and showed that cells within the tumor core were highly dynamic and display directionally correlated cell motion 50 , similar to our results described herein. Recent in silico based mathematical modelling of glioma cell dynamics by our group, showed that only elongated cells, but not spherical cells, are able to form organized aligned cellular structures in a cell-density dependent manner 47 . Our modeling studies strongly support our in-vivo and ex-vivo data described in this manuscript.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding characteristic features of glioma cells emerges as an important path to reveal the heterogeneity of GBM microenvironment to provide therapeutic approaches that successfully target the right subsets of glioma cells in GBM and eventually maximize efficacy and minimize the side effects of the applied therapy [5][6][7][8]. Glioma cells display striking cellular heterogeneity by changing their morphology [9][10][11], nuclear volume [12][13][14], cell-cell adhesion [15,16], cellular interaction [17], cytoskeleton organization [18][19][20][21], and by performing epithelial-to-mesenchymal transitions [22][23][24][25][26]. To characterize dynamic variations of glioma cells in the GBM microenvironment without altering genetic and phenotypic properties of the cells, we need to develop adequate tools [10].…”
Section: Introductionmentioning
confidence: 99%
“…Glioma cells display striking cellular heterogeneity by changing their morphology [9][10][11], nuclear volume [12][13][14], cell-cell adhesion [15,16], cellular interaction [17], cytoskeleton organization [18][19][20][21], and by performing epithelial-to-mesenchymal transitions [22][23][24][25][26]. To characterize dynamic variations of glioma cells in the GBM microenvironment without altering genetic and phenotypic properties of the cells, we need to develop adequate tools [10]. Precisely quantifying heterogeneity of glioma cells might contribute to reveal distinct invasive and aggressive subpopulations of glioma cells in the population [10].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, amyloid-like peptides featuring these favorable nanomechanical properties as well as an intrinsic bioactivity could be appropriate scaffolds for mimicking concentration gradients of the ECM. 23 Functionalization of the amyloid-scaffold e.g. with certain ECM protein-derived epitopes such as the laminin-derived peptide sequence RGD can further increase their bioactivity.…”
Section: Introductionmentioning
confidence: 99%